2019
DOI: 10.1021/acs.energyfuels.9b01457
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Depolymerization of a Lignin-Rich Corncob Residue into Aromatics in Supercritical Ethanol over an Alumina-Supported NiMo Alloy Catalyst

Abstract: A one-pot process for the depolymerization of lignin-rich corncob residue (LRCR) is investigated in supercritical ethanol over an alumina supported NiMo (NiMo/Al) alloy catalyst. The LRCR, as a major by-product in corncob enzymatic hydrolysis process, was completely liquefied and effectively transformed into aromatic compounds without the formation of tar or char under optimal reaction condition. Reaction temperature, time, solvent and initial hydrogen pressure have significant effects on the depolymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
(80 reference statements)
1
19
0
Order By: Relevance
“…These unsupported nickel catalysts with eliminating the mass transport limitation of the support achieve the complete liquefaction and efficient depolymerization of EHL, obtaining the highest monomer yield of 28.5 wt %, which is much higher than that obtained in previous works. 18,19 The effects of the decomposition temperature and atmosphere of nickel formate on the monomer yield are examined. The roles of ethanol and catalyst as well as the reaction pathway of the primary monomers are also discussed.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These unsupported nickel catalysts with eliminating the mass transport limitation of the support achieve the complete liquefaction and efficient depolymerization of EHL, obtaining the highest monomer yield of 28.5 wt %, which is much higher than that obtained in previous works. 18,19 The effects of the decomposition temperature and atmosphere of nickel formate on the monomer yield are examined. The roles of ethanol and catalyst as well as the reaction pathway of the primary monomers are also discussed.…”
Section: Introductionmentioning
confidence: 92%
“…Wang et al 18 employed 5 wt % Ni/C catalyst to depolymerize EHL and obtained an aromatic monomer yield of 12.1 wt % in methanol at 240 °C for 4 h with 3 MPa H 2 . Bai et al 19 reported the depolymerization of EHL with 15 wt % Ni/Al 2 O 3 and obtained an aromatic monomer yield of 10.3 wt % in ethanol at 320 °C for 7.5 h under 2.8 MPa H 2 . Nevertheless, the novel nickelbased catalyst with high activity needs to be further explored in order to obtain higher monomer yield.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Bai et al reported the depolymerization of lignin-rich corncob residue (LRCR) in supercritical ethanol at 320 C for 7.5 h with a yield of 147.9 mg g À1 (14.79 wt%) for alkylphenol. [20] Jiang et al used isopropanol as solvent and an in situ hydrogen source for the depolymerization of cellulolytic enzyme corn stover lignin and got a highest total monophenols yield of 8.14 wt% over Ni 50 Pd 50 /SBA-15. The yield of phenolic monomers was quite limited though bimetallic supported catalysts were applied.…”
Section: Effect Of Solvent Ratio and Timementioning
confidence: 99%
“…The conditions were 27.6 bar of hydrogen in supercritical ethanol at 320 °C for 7.5 h and a NiMo−Al alloy catalyst. 21 As can be seen from previous research, most of the work reporting NiMo or any other catalysts to convert lignin or its monomers focus on high pressure in batch reactors with reaction times exceeding 6 h. Comparatively, for our case, the residence time in a continuous reactor at atmospheric pressure was only 5 s. Hence, in this study, we have focused on the atmospheric pressure, gas-phase conversion of softwood lignin that could be a cost-effective, industrially viable process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They obtained 255 mg of aromatics per gram of LRCR with 58% by weight of alkylphenols. The conditions were 27.6 bar of hydrogen in supercritical ethanol at 320 °C for 7.5 h and a NiMo–Al alloy catalyst …”
Section: Introductionmentioning
confidence: 99%